2023
DOI: 10.1055/s-0043-1764222
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Cervical Cancer Prevention: Real-World Scenario in India

Abstract: In spite of global falling trends, cervical cancer remains a major healthcare challenge for India, South Asia Association for Regional Cooperation region, and other low- and middle-income countries. Our survey was to document the real-world challenges that still exist in India. A total of 316 eligible and complete responses to the 21 questions were analyzed. Screening of mothers and vaccinating their daughters was considered as the most important strategy to prevent cervical cancer by 65.8% (208/316). Screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…A systematic review in India exploring the implementation of self‐collection found patient‐level barriers, including lack of knowledge and misconceptions, low prioritisation to screen and poor sample quality due to a lack of self‐efficacy outweighed provider‐ and systems‐level barriers 44 . Solutions to address patient‐level barriers centred around community engagement and education strategies, including access to self‐collection swabs for women to develop familiarisation with the test and to mitigate fears and misconceptions related to self‐collection 43 . These studies provide contextualisation to our findings on barriers to women's screening participation and views of self‐collection in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review in India exploring the implementation of self‐collection found patient‐level barriers, including lack of knowledge and misconceptions, low prioritisation to screen and poor sample quality due to a lack of self‐efficacy outweighed provider‐ and systems‐level barriers 44 . Solutions to address patient‐level barriers centred around community engagement and education strategies, including access to self‐collection swabs for women to develop familiarisation with the test and to mitigate fears and misconceptions related to self‐collection 43 . These studies provide contextualisation to our findings on barriers to women's screening participation and views of self‐collection in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21]42 Similarly, a survey of 316 health practitioners in India found the most significant barrier to screening among their patient group was being asymptomatic, followed by embarrassment and fear of cancer diagnosis, and thus, there is a need to raise awareness to debunk myths and clarify facts related to cervical screening and HPV vaccination. 43 A systematic review in India exploring the implementation of self-collection found patient-level barriers, including lack of knowledge and misconceptions, low prioritisation to screen and poor sample quality due to a lack of self-efficacy outweighed provider-and systems-level barriers. 44 Solutions to address patient-level barriers centred around community engagement and education strategies, including access to self-collection swabs for women to develop familiarisation with the test and to mitigate fears and misconceptions related to self-collection.…”
Section: 35 Yearsmentioning
confidence: 99%
“…Awareness, screening, and early detection lead to improvement in mortality. 1,5 Our prospective study aimed to establish a community PAP smear lab as part of (demonstrable) healthcare reforms in rural India.…”
mentioning
confidence: 99%
“…Cervical cancer is second commonest cancer in rural Indian females. 1 This is most preventable cancer due to long biological course, identifiable precancerous lesions, and effective vaccine. 2 3 Other risk factors are younger age at marriage, number of pregnancies, genital hygiene, and tobacco consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation